Synthesis and Reactivity of Monocyclic Homoleptic Oligophosphanes. Issue 1 (19th November 2020) - Wellnitz, Tim; Hering‐Junghans, Christian
Abstract : This Minireview outlines the synthesis and reactivity of homoleptic, cyclic oligophosphanes, which have been known for more than 150 years. We will discuss a variety of (PR) n ( n = 3, 4, 5, 6) species and outline approaches towards their syntheses in the first part of this review. Then the unique reactivity of these inorganic ring systems will be discussed in detail with a focus on recent findings within the last 20 years. First ring expansion reactions will be described, which are mainly restricted to cyclotriphosphanes. Secondly, ring fragmentation will be highlighted, including phosphinidene transfer reactions. Furthermore, cyclooligophosphanes can be functionalized while retaining the parent ring structures. As oligophosphanes offer multiple donor sites, in a last part the coordination chemistry of these species is highlighted. We hope that this Minireview will spark further interest in this underexplored class of compounds as reagents in inorganic and organic synthesis, as well as the design of new P‐containing materials. Abstract : Homoleptic cyclooligophosphanes are an important class of inorganic ring systems. Herein we summarize their synthesis and reactivity with respect to ring fragmentation, ring expansion, ring functionalization and coordination chemistry.